“EU Perspectives: Is the EU Trying to Restart the European Integration of the Western Balkans” - Runcheva Tasev, Hristina (UACES (University Association for Contemporary European Studies), 2017)
European integration has been recognized as a key strategy for achieving peace and prosperity in the Western Balkans. The policy makers believe that the integration of this region in the European Union will have positive effects on long-term conflict management and therefore ten years ago, at the Thessaloniki summit, a full support to the integration of the of the Balkan states was stated. But, for many months the Western Balkans has been shaking of political instability, which has raised tensions to the highest levels, but still without the use of violence. Macedonia is imploding into a severe political crisis, which has the potential of becoming an inter-ethnic conflict, the tension between Croats, Serbs, and Bosniaks in Bosnia and Herzegovina has risen dangerously together with inflammatory rhetoric, unilateral provocative actions, and claims that Dayton is dead; Serbia is in a constant election campaign with the price constantly on the rise, thus emitting signals that inflame old wounds across the region. Montenegro is on the way to reach NATO, but Russia is having strong influence over the domestic policy and creating obstacles on its path. Albania is into deep political crisis and instability. In addition, for the first time in the newest history of EU enlargement the European Council ended the year with no conclusions about candidate states. The European integration does not work well in a region with so many unsolved problems from the past and such a strong geopolitical pressure. The paper will analyze the issue whether it is possible for the Western Balkans to restart the process of European integration, which has practically stopped, is there any political will and how will that affect the stability of the region.
Keywords: EU integration, Western Balkans, political crisis, conflict management.